Paratuberculosis vaccination causes only limited cross-reactivity in the skin test for diagnosis of bovine tuberculosis. - Joseba M Garrido (Public Library of Science (PLoS), 2013)
Although there is a wide consensus on the efficacy of paratuberculosis vaccination to limit economic losses, its use has been restricted because of its interference in the diagnosis of tuberculosis. Data from a vaccine clinical trial in the Basque Country (Spain) has been evaluated in relationship with bovine tuberculosis intradermal test results. The trial included two herds applying a Test and Culling strategy and five applying an inactivated vaccine. The vaccine was applied to animals of all ages present in each vaccinated herd when joining the trial, and then to all the replacers within their first three months of life. Yearly testing done with the comparative intradermal test (CIT) was applied to all animals older than 6 weeks. Between 2005 and 2011, the study generated 2,033 records from Vaccinated Herds (VH) and 2,252 from Test and Cull herds (TC). Pre-vaccination positive results rate was 2.40% among the 7 herds in the single bovine intradermal tuberculin test (BSIT). Two years later it rose to 20.42% in the VH and remained below at 0.75% in the TC. Applying the CIT reduced these rates to only 0.58% in the VH and to 0.25% in the TC ons. Regarding time since each animal joined the program, the proportion of positives to BSIT was variable and, in some cases, significantly different between time points. With regard to the age of vaccination, no significant differences were found between vaccination within the first year of life and afterwards. Vaccinated animals showed seventeen times more reactions than the non-vaccinated in the BSIT, but only four times more in the CIT. In conclusion, comparative intradermal test can be a useful tool to differentiate paratuberculosis vaccine cross-reactions from specific bovine tuberculosis reactions according to the European and Spanish legislation.